Estimation of Vent Radii From Video Recordings and Infrasound Data Analysis: Implications for Vulcanian Eruptions From Sakurajima Volcano, Japan - Dan Muramatsu; Koki Aizawa; Akihiko Yokoo; Masato Iguchi; Takeshi Tameguri (Geophysical Research Letters)
Abstract We estimated the vent radius within Showa Crater of Sakurajima volcano from ejection velocity and flow rate of gas‐particle mixtures. The ejection velocity was calculated from video recordings, and the flow rate and volume from infrasound data. Based on the assumption that the vent shape does not change during an explosion, the vent radius was estimated from 201 impulsive Vulcanian eruptions at Showa Crater, yielding values of 6.4–42.3 m (median 23.8 m), which is comparable with the width of fresh lava capping the vent, as photographed from a helicopter. Long‐term changes in vent radius (i.e., over several months) show a relationship with magma accumulation within a reservoir 2–5 km beneath the crater. If the top of the conduit is assumed to be cylindrical, then the vertical extent of the gas‐rich zone is estimated to be 120 m, which may reflect the depth of gas accumulation and buildup of significant overpressure.